THE CHOICE OF PROTECTIVE COATING APPLICATION METHOD - A. M. Amouei; G. R. Mirhosseini; A. Jafari; A. I. Tarasov (Научный вестник МГТУ ГА)
The article deals with the application different methods of combination of coating on the GTE turbine working blades. The results of the experimental research on the application of the protective coating on the GTE turbine working blades are presented and the samples with coating were tested to determine the resulting coating quality.